THE MAINTENANCE OF ENDURANCE PERFORMANCE AMONG TAEKWONDO ATHLETES DURING THE COMPETITION PERIOD - Tirtawirya, Devi; Rohidi, Rohendi; Hidayah, Taufik (The Journal of Educational Development, 2017)
Taekwondo kyorugy is a martial arts fight conducted one-on-one using the standard rules and performed for 2 minutes 3 times a round. In the case of equal value,  there is an additional round with sudden death system. The type of taekwondo kyorugy/fight motion is always done with speed and explosive motion. Therefore, the energy system used is predominantly aerobic. During the competition period, it needs exercise program with a model that is close to the real game but can maintain anaerobic endurance performance up to the main competition. This study was designed using the method of action research where the training program was run and simultaneously observed and evaluated to obtain the desired results. After that, the test results were processed to result in the average values then narrated as it is shown in the existing graphs. The Running-based Anaerobic Sprint Test (RAST) was implemented for durability tests. The results of the discussion on the chart competition period did not show significant change. This condition indicates that training program can maintain endurance performance during the competition period. In the discussion on the competition period, there are findings which strongly confirm the assumption that taking a rest is as important as doing the exercise itself. It is caused by the fact that some tests which were repeated because of lack of rest and the result were not good, but after adequate rest was given the result was much better. Based on the results of the exercise using the four physical exercise models employing the taekwondo approach, techniques, and tactics, it was proven that it was capable of maintaining the aerobic endurance performance during the competition period. It is hoped that athletes will quickly adapt to the actual match.